Evolution of the availability of Information and Communication Technologies in primary health care in Brazil, 2012 to 2018 - Janaína Duarte Bender; Luiz Augusto Facchini; Luís Miguel Velez Lapão; Elaine Tomasi; Elaine Thumé (Revista Brasileira de Epidemiologia, 2024)
ABSTRACT Objective: To verify the evolution of the availability of information and communication technology equipment and inputs in primary health care services that participated in the external evaluation of the Access and Quality Improvement Program in Primary Care and its distribution according to context characteristics social and geographic. Methods: Cross-sectional study, analyzed the distribution of information and communication technology equipment in basic health units in Brazil, during the three cycles (2012 to 2018) of the Program for Improving Access and Quality in Primary Care. The variables were examined at the municipal level and stratified by geopolitical region. Univariate analysis was performed, using the chi-square test and testing the distributions of exposures among themselves and between the outcome and exposures. Results: The availability of information and communication technology equipment increased from 9.4% (2012) to 17.5% (2018), with emphasis on the Southeast and South regions, in municipalities with a population size of up to 10,000 inhabitants², with greater family health coverage and high/very high HDI-M. Over the period from 2012 to 2018, basic units joined the program and increased availability of information and communication technologies, such as Internet access, which ranged from 45.2% (n=6,249) to 74.0% (n=21,423), with emphasis on the Northeast region, which increased from 19.1% (n=970) to 58.8% (n=7,087). Conclusion: Investment in technologies and constant evaluation of primary care in the country is necessary, contributing to its strengthening.